2021
DOI: 10.1155/2021/5954343
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence-Based Analysis on Observation for Nursing Care of Patients with Intra-Aortic Balloon Pumping

Abstract: In this study, data analysis was performed on 52 patients. According to the different outcomes and discharge diagnosis of patients, data on sedative use, emotions, behavioral abnormalities, hearing loss, pain, total time on board the IABP (intra-aortic balloon pumping), and days of hospitalization of patients were collected. The data were subjected to frequency analysis, paired chi-square analysis, chi-square test, Poisson regression analysis, and stepwise regression analysis. Some findings of the analysis inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%